2020
DOI: 10.3390/cells9061361
|View full text |Cite
|
Sign up to set email alerts
|

Current View on EpCAM Structural Biology

Abstract: EpCAM, a carcinoma cell-surface marker protein and a therapeutic target, has been primarily addressed as a cell adhesion molecule. With regard to recent discoveries of its role in signaling with implications in cell proliferation and differentiation, and findings contradicting a direct role in mediating adhesion contacts, we provide a comprehensive and updated overview on the available structural data on EpCAM and interpret it in the light of recent reports on its function. First, we describe the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 100 publications
(198 reference statements)
0
19
0
Order By: Relevance
“…Mapping of the TACE cleavage sites onto the EpEX dimerization surface (Tsaktanis et al, 2015) indicated that the cleavage by TACE can take place only when EpCAM is in a monomeric state. Molecular docking of the TACE catalytic domain on EpEX (Gaber, Lenarčič & Pavšič, 2020) also supports this hypothesis by demonstrating that EpCAM dimerization sterically hinders access of TACE to the cleavage site. However, the effect of EpCAM oligomeric state on susceptibility to TACE cleavage has never been experimentally addressed, partly due to the inability to manipulate the EpCAM/EpEX oligomeric state.…”
Section: Introductionmentioning
confidence: 78%
“…Mapping of the TACE cleavage sites onto the EpEX dimerization surface (Tsaktanis et al, 2015) indicated that the cleavage by TACE can take place only when EpCAM is in a monomeric state. Molecular docking of the TACE catalytic domain on EpEX (Gaber, Lenarčič & Pavšič, 2020) also supports this hypothesis by demonstrating that EpCAM dimerization sterically hinders access of TACE to the cleavage site. However, the effect of EpCAM oligomeric state on susceptibility to TACE cleavage has never been experimentally addressed, partly due to the inability to manipulate the EpCAM/EpEX oligomeric state.…”
Section: Introductionmentioning
confidence: 78%
“…EpCAM and EpCAM2/Trop2 are single transmembrane glycoproteins, with a unique sequence and a unique 3D structure (reviewed in [ 13 ]). They are unrelated to any known CAM.…”
Section: General Features Of Epcammentioning
confidence: 99%
“…This result remains puzzling, since, as we will see below, EpCAM has a clear pro-adhesive activity, at least in the context of early embryos. As for the putative homotypic binding, however, recent extensive biochemical tests have failed to detect any hint of such interaction, and it was thus concluded that EpCAM is unlikely to be a bona fide CAM [ 21 ], reviewed in [ 13 ].…”
Section: General Features Of Epcammentioning
confidence: 99%
“…Both are promising targets in carcinoma diagnosis, prognosis, and therapeutic approaches [ 4 , 5 ], which calls for a detailed functional and structural comparison. While EpCAM has already been structurally characterized [ 6 , 7 , 8 ], no equivalent structural data have been available for Trop2 until now.…”
Section: Introductionmentioning
confidence: 99%